ENGLISH BASED SMART INNOVATION THROUGH INTERACTIVE VIDEO AT BHINA KARYA AND SATYA KARYA KARANGANYAR VOCATIONAL SCHOOLS - Erma Nurhayati Firdaus; Rahaju Muljo Wulandari; Liss Dyah Dewi Arini (JF Publisher, 2023)
Learning media is one of the very important learning components as a bridge in the delivery of material. The use of media in learning can have a positive impact and tremendous benefits in facilitating the student learning process. Learning media is also an indispensable basis for the success of the learning process. The aims of this study were (1) to determine student learning outcomes using conventional media based on animated videos (2) to analyze differences in learning outcomes between students using conventional media and animated videos. The stages of this research method are quasi-experimental research with pretest and posttest designs. The subjects of this study were students of class X at SMK Bhina ​​Karya Karanganyar and SMK Satya Karya Karanganyar. Taking the research class through random sampling technique based on the adjustment of the material to the class curriculum. Activities in data analysis include data processing activities and statistical analysis. This test was carried out on pre-test and post-test data, changes in post-test scores from pre-test scores on the experimental group. The conclusion of this study is that the learning model through learning media through interactive video is able to motivate students so that learning achievement can increase. Students gave a positive response to the implementation of the learning model using interactive videos.